2003
DOI: 10.1002/jmv.10525
|View full text |Cite
|
Sign up to set email alerts
|

Effector HIV‐specific cytotoxic T‐lymphocyte activity in long‐term nonprogressors: Associations with viral replication and progression

Abstract: Ex vivo effector cytotoxic T-lymphocyte (CTL) activity was assessed in 27 members of the Australian Long-Term Nonprogressor cohort and correlated with genetic, virological, and immunological markers. The 27 individuals were antiretroviral naive with CD4(+) T-cell counts of >500 cells/ microl for more than 8 years after human immunodeficiency virus type 1 (HIV-1) infection. Effector CTL activity was determined using a standard ex vivo chromium release assay. Individuals with CTL activity (HIV-1 env(IIIB) or pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Our findings indicate HIV-specific cytotoxic cells are readily detected directly ex vivo from the PBMC of chronically infected patients, in agreement with other reports using bulk lysis assays (23,24,26,40), and in contrast to others reporting ex vivo cytolysis is impaired or not detectable (27,29,30). This discrepancy may be due to the clinical status of the patient groups analyzed in the different studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings indicate HIV-specific cytotoxic cells are readily detected directly ex vivo from the PBMC of chronically infected patients, in agreement with other reports using bulk lysis assays (23,24,26,40), and in contrast to others reporting ex vivo cytolysis is impaired or not detectable (27,29,30). This discrepancy may be due to the clinical status of the patient groups analyzed in the different studies.…”
Section: Discussionsupporting
confidence: 93%
“…The correlative trend between increased viral load and higher HIV-specific cytotoxic cell frequencies found in our study agrees with previous reports that measured target cell lysis using the 51 Cr release assay (26) or granzyme A expression (44). Thus, it appears likely that when HIV is not effectively contained, the resulting rise in viral load induces a higher frequency of cytotoxic cells detectable ex vivo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among human immunodeficiency virus (HIV)-infected persons, a small percentage maintaining CD4 T-cell counts of Ͼ500 cells/l for more than 10 years without receiving antiretroviral therapy are known as long-term slow progressors (SPs) (9,10,12,13,22). The factors involved in the long-term survival of these patients have been the subject of intense investigations since these factors may provide information important in the development of HIV-1 vaccines and treatments.…”
mentioning
confidence: 99%
“…Several studies show that exposed but uninfected individuals have HIV-1-specific CTLs without detectable antibodies [3,4] . In addition, data show a strong correlation between a high frequency of HIV-1-specific CTLs with a low HIV-1 viral titer and a slow disease progression in chronically HIV-1-infected individuals [5,6] . It has also been shown that CTL numbers decline in association with progression of AIDS [5] .…”
mentioning
confidence: 94%